PENGEMBANGAN BUKU PANDUAN ALAT MUSIK PIANIKA PADA PEMBELAJARAN SBdP UNTUK SISWA SEKOLAH DASAR NEGERI 1 DADAPAN - Mara, Istiana; Gutama, Andika; Rahayunita, Cicilia Ika (Cahaya Ilmu Bangsa Institute, 2024)
In the learning of Cultural Arts and Skills (SBdP) focusing on understanding tempo markings and pitch, particularly in the musical art of playing the melodica, students find it difficult to grasp the material being taught, and there is a lack of proper time management. Additionally, not all teachers have qualifications in musical arts. This type of research is qualitative, conducted through interviews, observations, and validation questionnaires from experts in content, media, and language. From the study on the Development of a Melodica Instruction Guide for SBdP Learning in Elementary Schools, through the validation testing process, the following results were obtained: media experts rated it with an average feasibility percentage of 90%, content experts 89%, and language experts 93%, all categorized as